The associated factors for spontaneous intranodular hemorrhage of partially cystic thyroid nodules: A retrospective study of 101 thyroid nodules. Issue 51 (18th December 2020) - Yang, Haizhen; Zhao, Shuangshuang; Zhang, Zheng; Chen, Yanwei; Wang, Keke; Shang, Mengyuan; Chen, Baoding
Abstract : Abstract: Spontaneous intranodular hemorrhaging in benign partially cystic thyroid nodules was reported to cause neck swelling, difficulty swallowing, and other oppressive symptoms attributed to their growing progressively at high rates. In our study, the risk factors for hemorrhaging in these nodules were investigated. We retrospectively analyzed benign partial cystic thyroid nodules from September 2017 to December 2019, and divided them into 2 groups according to the occurrence of intranodular hemorrhage. Age, gender, follow-up time nodules initial maximum diameter, blood supply, spongiform content, nodules solid components, and internal solid portion were compared between the 2 groups at the first ultrasound examination. Chi-Squared and multivariate analysis were performed to evaluate the association of hemorrhage with clinical and ultrasonographic characteristics. ROC analysis was performed to evaluate the utility of factors in predicting hemorrhage. There were 59 occurrences of intranodular hemorrhage, which were associated with abundant blood supply, spongiform contents, and unsmooth margin of the internal solid portion. After multivariate analysis, abundant blood supply, and spongiform content were independent predictors for hemorrhage. In ROC analysis integrating these predictors, the sensitivity was 62.7% and specificity was 95.2% with the AUC 0.881. Partially cystic thyroid nodules with abundant blood supply, non-smooth margin of the internal solid portion and a spongiform internal content were apt to spontaneous intranodular hemorrhaging, which can be recognized as soon as possible by ultrasound.